ORIENTASI MATERI AJAR MATA PELAJARAN AKIDAH AKHLAK PADA MADRASAH ALIYAH : (Analisis Kritis Perspektif Visi Islam Toleran, Anti Kekerasan Seksual\ dan Anti Perundungan) - Ma’rufin; Jamali; Muslihudin (JIP: Jurnal Ilmu Pendidikan, 2024)
Nowadays educational institutions are faced with problems of intolerance, sexual violence and bullying. One of the causes is the lack of understanding of educational stakeholders, or even not a comprehensive understanding of intolerance, sexual violence and bullying. This research discusses how the teaching materials for the Aqidah Akhlak Madrasah Aliyah subject present material related to this problem as a form of overcoming and preventing it. In the study of the Madrasah Aliyah Aqidah Akhlak subject textbook, it was discovered that on the issue of intolerance, this book presents a complete and complete outline. This can be seen from the discussion of washatiyah Islam and the recommendation for harmony between religious communities by prioritizing the attitudes of tasamuh, musawah, tawasuth and ukhuwah. On the other hand, the presentation of material related to sexual violence and bullying in this book is not the main material that specifically discusses the two, but only presents secondary material that is related, such as the story of the Prophet Luth (AS.), and his people, the manners of dressing, walking, adorning themselves. , avoid acts of adultery, cunning, injustice, discrimination and social etiquette among teenagers. Thus, the conclusion of this research is that it seems that the Ministry of Religion already has a structured and systematic formula for presenting intolerance material. This is because the issue of intolerance is the work area of ​​the Ministry of Religion.